INTERVENSI MENDONGENG CERITA RAKYAT UNTUK MENINGKATKAN NASIONALISME ANAK DI PANTI ASUHAN - Imanuel , Dastin; Billy Nugroho; Daffydd Kenneth; Alessandro Bernard; Wiradika; Sri Tiatri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
This study aims to address the decline in the sense of nationalism among children in orphanages through the intervention of storytelling folk tales rich in Pancasila values. The methodology employed involves pre-test and post-test measures to assess changes in nationalism attitudes before and after the intervention. The intervention consisted of screening folk tale films, such as Lutung Kasarung and Si Pitung, followed by traditional storytelling and a psychoeducation session themed